KEPEMIMPINAN KEPALA SEKOLAH DI ERA KECERDASAN BUATAN DALAM PENGELOLAAN PEMBELAJARAN DAN ADMINISTRASI - Didit Darmawan; Aditiya Purnama; Rizqi Ihsan Maulana; Sinta Nurya; Rahayu Mardikaningsih (CV. Lafadz Jaya, 2026)
This article presents a conceptual study of school leadership in the age of artificial intelligence in education. The discussion focuses on how principals can prepare their institutions and human resources for AI driven changes in teaching, assessment, and administration. The paper proposes that school leaders articulate a clear vision of AI as a supportive tool aligned with educational goals, guide curriculum adaptation to include AI literacy and ethical reflection, and design structured professional development for teachers regarding AI capabilities and limitations. It also argues that principals should establish policies regulating classroom use of AI, protect data privacy, and preserve the humanistic essence of education by safeguarding teacher student relationships and dialogic learning. Furthermore, the article highlights the need for participatory leadership structures, critical engagement with technology providers, and transparent communication with parents. The proposed framework aims to serve as a normative reference for principals and policy makers seeking to steer schools through AI related disruptions while maintaining educational values.